Reproductive Performance of Glossina palpalis gambiensis (Diptera: Glossinidae) when fed frozen or fresh bovine blood meals - Soudah Boma; Ernest Wendemanegde Salou; Prudenciène Agboho; Cene Bila; Simon Kabore; Abdoul Rahim Sabo; Zakaria Bengaly; Charles Guiguigbaza Kossigan Dayo (European Scientific Journal, ESJ, 2022)
The tsetse and trypanosomoses control by sterile insect technique (SIT), requires mass production of quality tsetse pupae and consequently high-quality blood meal for the fly feeding. The reproductive performances of Glossina palpalis gambiensis (Diptera : Glossinidae), fed frozen or fresh blood meals has been studied. Three diets of slaughtered bovine blood stored at -18 °C for six months (R6), three months (R3) and one month (R1) were used in the present investigation. Fresh blood samples stored at 4°C and renewed every four days were used as control (R0). The defibrinated blood was packaged in batches of 30 x 20 ml vials. For each blood meal, 30-day feeding tests were conducted at the beginning and end of freezing. All blood meal was irradiated using 137 caesium irradiation before being used. The parameters monitored daily were: the number of dead flies (fed and unfed), the number and weight of pupae and the emergence rate. No difference in survival rates was observed for the three regimes (df: 15; Chi-square: 7.53; p > 0.05), on average 32.1% (R0), 32.4% (R6), 37.5% (R3) and 38.2% (R1). However, flies fed with the six-month-old frozen blood were less efficient in pupa production (df: 3; F: 6. p < 0.001) and pupae weight (df: 3, F: 3.24, p < 0.05) compared to the control. The mortality rate was affected by the duration of freezing: 26.7% for R6 and 8% for the other diets (p <0.05). The implications of our results in terms of blood meal management for efficient production of insectary pupae were discussed.